PASCH and Non-PASCH Students’ Internal and External Learning Motivation - Baiq Almira Winda Rahmasari; Edy Hidayat (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
The purposes of this research are to describe the factors of the PASCH and non-PASCH students’ internal and external motivation to learn german and to describe the PASCH- and non-PASCH teacher’s role on motivating the students to learn german. This research uses the descriptive qualitative method. The results of this research show that internal factors that underlie students' learning motivation are shown among others by the reasons for students why they learn German, students' interest in German country and culture, the importance of German for students, the enthusiasm of students during german lesson, and the effort of the students to improve their german. Meanwhile, PASCH program is an additional factor of the PASCH students extrinsic motivation while for non-PASCH students, the teachers have a more dominant role as a factor of their extrinsic motivation, the teachers of PASCH and non-PASCH schools have a big role on motivating the students externally.